Transverse strength of railway tracks: part 1. Planning and experimental setup (Fracture and Structural Integrity, 2014)
Several studies have been carried out until now by various Research Agencies and Railway Administrations to quantify the effects of the track-bed geometrical characteristics on the transverse strength of the track. Unfortunately, not all the possible scenarios in terms of track components, track-bed cross profile, operating conditions etc. have been investigated and not all the relevant variables have been directly measured.Therefore data available from the literature have different degrees of reliability. With the aim of enlarging the knowledge on the track stability and covering much of the possible relevant scenarios, an experimental research program has been developed in the framework of a cooperation between RFI, Italcertifer and DII.In order to perform the investigation under quite general conditions and to reduce the experimentation costs, n. 28 significant scenarios have been identified and reproduced on as many independent track segments. Byapplying on each track segment a transversal load, the strength of the ballast-sleeper interface has beendetermined. The results relative to the first four scenarios are presented in terms of applied load vs. lateral track displacement diagrams and in more synthetic numerical tables.
Keywords: Railway track